The prevalence of and factors associated with antipsychotic polypharmacy in patients with serious mental illness: Findings from a cross-sectional study in a low-middle income country - Armstrong, Kerryn (Department of Psychiatry and Mental Health, 2018)
Rationale: Antipsychotic polypharmacy (APP) appears to be a common practice worldwide despite treatment guidelines advising against the practice for most patients in view of lack of evidence and possible risk of harm. Our study aimed to address deficiencies in local and international research by examining the current prevalence of APP in a South African context and investigating a broad range of patient, illness and treatment characteristics that may be associated with the practice. In doing so, we aimed to provide an indication of possible areas to be addressed in order to improve local mental health care practice. Methods: We conducted a cross-sectional study of discharge records using Valkenberg Hospital's electronic patient database. We collected data on patient, illness and treatment characteristics for patients discharged on one or more antipsychotic agent from January to June 2014. Hierarchical multivariable logistic regression analysis was conducted to assess the relationship between APP and demographic and clinical variables and prescription patterns were analysed. Results: Discharge records of 565 patients were examined. The prevalence of APP in our study population was 29.03% (95% CI= 25.31%-32.96%). Analysis of demographic and clinical characteristics revealed that age>29, male sex, diagnosis of schizophrenia compared to bipolar and substance-induced disorders, co-morbid intellectual disability, co-morbid substance use, greater number of hospital admissions and high-dose prescribing were significantly associated with APP. While highest rates of APP in patients with schizophrenia and schizoaffective disorders occurred, APP was also observed in a number of patients with bipolar and substance-induced disorders. Prescription patterns demonstrated the prominent use of first-generation antipsychotics and long acting injectables in APP combinations. Patients receiving APP were significantly more likely to have anticholinergic agents and sodium valproate co-prescribed in their treatment regimen. Discussion: The prevalence of APP found in our study is fairly high in comparison with international rates. Antipsychotic prescription patterns reflect a complex interplay among patient, illness and treatment characteristics of our population. Our findings indicate that patients receiving APP may be those with greater illness severity, complexity, chronicity and treatment resistance, with complicating factors including co-morbid substance use involved. While APP is most common in patients with schizophrenia, antipsychotics may also be used in combination to manage mood and psychotic symptoms in patients with schizoaffective, bipolar and substance-induced disorders. The frequent use of long acting injectables in combinations may suggest concern over compliance in our population. The positive associations of APP with high-dose prescribing and co-prescription of anticholinergic medication contributes to concern over the safety of APP. Conclusion Our study suggests concern over current local practice in that combination antipsychotic agents were prescribed for a number of patients with a range of psychiatric diagnoses without sufficient evidence for efficacy of this practice and at possible cost of increased adverse effects. Additional research is needed examining the practice of APP across diagnoses, focusing on the multiple aspects affecting local practice and various contributing factors that could be targeted for intervention. This would be a positive step towards improving the quality of our service and providing optimal patient management in a resource-limited setting.